Exploring the Effectiveness of Portfolio Assessment in Developing EFL Students’ Reflective Writing. A Case Study of Second year LMD Students of English, University of Laghouat - Bouakkaz, Achoura; Larabi, Nacira; Boumediene, Houda (Faculty of Letters and Foreign Languages Department of English, 2017)
The primary focus of this work is to explore the effectiveness of portfolio assessment in developing EFL students‟ reflective writing. In order to reach this objective, an experimental study was conducted. The sample consisted of 100 second year students of English at the University of Amar Thelidji -Laghouat. Data were collected through the following experimental tools: Pre-Post Writing Test, in which students were asked to write about ten topics, Pre/Post Self-Reporting Questionnaire, and interview. This study took place during the second semester of the academic year 2016-2017. The findings show that the reflective writings of students were improved after the use of portfolio assessment method. These confirm our hypothesis that portfolio assessment strategy has significant effects in developing students‟ reflective writing in terms of both process and product